REVITALIZATION OF VILLAGE CHICKEN FARMING MSMES: PRODUCTION AND ENTREPRENEURSHIP INNOVATION TOWARDS INTEGRATED VILLAGE AGRIBUSINESS - Iwan Hermawan; Gita Hindrawati; Sartono Sartono; Suharmanto Suharmanto; Inayah Inayah (International Journal of Engagement and Empowerment (IJE2), 2026)
Mbangkong Village is predominantly inhabited by young people, accounting for 58% of the total population. Most of the youth in this village, especially women, do not pursue higher education and tend to marry at an early age. This socio-demographic condition has limited the community's livelihood choices, which are primarily concentrated in agriculture, animal husbandry, and micro, small, and medium enterprises (MSMEs). One of the MSMEs that partnered in this community engagement program is a free-range native chicken farming business that generates monthly revenue of IDR 8–10 million. Although market demand for native chicken continues to grow, the business faces a 35% supply gap that has yet to be addressed. The partner MSME faces several core challenges, including: (1) inadequate security of the farm area due to the absence of proper fencing, making it vulnerable to external threats; (2) limited managerial capacity in business planning, management, and evaluation, which are still carried out using traditional methods; and (3) lack of product diversification, with income solely dependent on the sale of live chickens and eggs, without any value-added products. This community engagement program aims to provide comprehensive solutions through three main approaches: (1) improving production capacity by building or repairing chicken coops and securing the farm area to make it safer and more productive; (2) providing entrepreneurship management training for MSME actors and local business communities in Mbangkong Village to enhance their business sustainability skills; and (3) developing derivative products from native chicken to increase added value and expand market reach. The expected outcomes of this program include: (1) improved farm safety and productivity through physical infrastructure enhancement; (2) strengthened managerial knowledge and skills of the MSME partner through entrepreneurship training; and (3) increased business income through product diversification and market development. Ultimately, this program is expected to strengthen the MSME partners' economic resilience and promote sustainable local economic growth.